Comparison of Measurement of Central Corneal Thickness with Spectral Domain Optical Coherence Tomography and Standard Ultrasonic Pachymeter in Premature Infants - Emre Hekimoglu; Muhammet Kazım Erol; Devrim Toslak; Deniz Turgut Coban; Berna Doğan; Ozgur Yucel (Journal of Ophthalmology)
Purpose. To evaluate the repeatability of measurement of central corneal thickness (CCT) by spectral domain optical coherence (SD-OCT) in premature infants and compare it to CCT measurement by ultrasonic pachymetry (USP). Methods. Three CCT measurements of the left eyes of 50 premature infants were obtained by SD-OCT using the iVue system. 10 CCT measurements of each 28 left eyes of 28 infants were obtained by USP using the Pacscan 300P system. Bland-Altman plots were developed and the limit of agreement (LoA) was determined to compare the mean of the SD-OCT and USP measurements. Results. No statistically significant difference was found among the 3 CCT measurements by SD-OCT. Both USP and SD-OCT have been performed for only left eyes of 28 of the 50 babies. Those results have been compared with each other. A statistically significant difference was found between the mean CCT measurements by SD-OCT and USP (p<0.05). The LoA between the SD-OCT and USP measurements ranged from 11.4 to −64.1. Conclusions. CCT can be measured using the iVue SD-OCT system with a high level of repeatability. Although measurement of CCT by SD-OCT and USP is highly correlated, the 2 systems cannot be used interchangeably in premature infants.